Accidental Revitalization? Looking at the Complex Realities of Union Renewal. (December 2017) - Foster, Jason
This article outlines a union renewal case study with unexpected circumstances. It examines a local that underwent significant renewal in a context where renewal would normally not be expected. It did so by significantly altering its practices while retaining a stable leadership and highly centralized structure. This unexpected renewal is explained through the application of a referential unionisms framework. The article coins the term accidental revitalization to describe the case, arguing the intentionality for reform lies not in design, policy, or upheaval, but instead in an extension of logics constructed through narrative resources mobilization.